Risk Factors Associated with Postoperative Outcome of Congenital Anomalies - Harsali F. Lampus; Candy Candy; Leo Rendy; Sabrandi P. Saputra (e-CliniC, 2022)
Abstract: Mortality rate of newborns with congenital abnormalities worldwide is still high in the first four weeks after birth every year. This study aimed to obtain the profile of patients with congenital anomalies related with mortality after surgery at the Pediatric Surgery Department, Prof. Dr. R. D. Kandou Hospital, Manado, Indonesia. This was a descriptive and retrospective study. There were 98 samples during 2019 to 2021. Dependent variable was postoperative mortality outcome and independent variable risk factors were sex, gestational age, birth weight, and length of stay. Data were analyzed using univariate method. The results showed that postoperative death was 27.6%, and sex ratio was equally distributed (male 51%; female 49%). Gestational age was pre-dominanly aterm 77.5% vs preterm 22.5%. Birth weight of â‰¥2500 g was 77,5% and low birth weight (<2500 g) was 22.5%. Hospitalitation length of stay probably less than two weeks was 82.7%. Pediatric surgical congenital anomalies were as follows: Hirchsprung Disease (15.1%), anorectal malformation (41.7%), lateral inguinal hernia (11.3%), diaphragm hernia (3.1%), omphalocele (2.1%), gastroschisis (2.1%), undescended testis/UDT (4.1%), invagination (4.1%), duodenal atresia (3.1%), ileojejunal atresia (4.1%), esophageal atresia (5.1%), biliary atresia (1%), and mechanical bowel obstruction (3,1%). In conclusion, in the last two years, pediatric surgery services in surgical congenital anomalies had overall mortality rate of 27,6% without sex predominantly. Most patients were aterm babies with normal birth weight and relatively short length of stay.Keywords:Â  congenital anomalies; postoperative outcome